Exploring the Pharmacological Potential of Achyranthes aspera (Latzeera): A Complete Investigation of its Anticancer, Anti-Microbial and Antioxidant Activities - Arijit Chaudhuri; Biswajit Dash; Ashish Sarkar; Afrin Alam; Ayush Garg; Shivani Devi; Ankita Sharma; Varsha Chauhan; Tanbeer Kaur; Yashna Bawa (Pharmacognosy Research, 2025)
Background: A medicinal herb called Achyranthes aspera has been used for centuries to treat a wide range of illnesses. By assessing its antineoplastic, anti-microbial and antioxidant properties. This study sought to thoroughly explore Achyranthes aspera pharmacological potential. Materials and Methods: Antibacterial activity against a panel of bacterial strains was assessed using the disc diffusion method. To ascertain cell viability in cancer cell lines, anti-cancer activity was assessed using the MTT assay. The antioxidant activity of the plant extract was assessed by its capacity to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals. Results: Achyranthes aspera extract showed encouraging antibacterial efficacy against specific bacterial strains, however not as strong as the common antibiotic, ciprofloxacin. The MTT assay indicated possible anti-cancer efficacy by showing a notable dose-dependent reduction in cancer cell lines' cell viability. Through the scavenging of free radicals, the extract from Achyranthes aspera also demonstrated strong antioxidant activity. Conclusion: The pharmacological potential of Achyranthes aspera is strongly supported by this investigation, confirming its historic use in treating a variety of illnesses. Promising antioxidant, antimicrobial and anti-cancer properties were demonstrated by the plant extract. In order to determine the bioactive components, clarify the underlying mechanisms of action, assess the protection and efficacy of Achyranthes aspera extracts in preclinical, clinical contexts, these findings call for additional research.
Keywords: Achyranthes aspera; Anti-cancer; Anti-microbial; Antioxidant